Fifth Order Improved Runge-Kutta Method for Random Initial Value Problems - Almbrok Hussin Alsonosi Omar , Iman Aissa Alghannay Ahmed (Journal of Pure & Applied Sciences, 2018)
When the initial conditions of differential equations are random in natural, mathematical description of the solution in terms of initial conditions must be modified by considering the initial conditions as random variable having a particular statistical distribution. In this paper, the fifth order improved Runge-Kutta method (IRK5) is modified for the approximation of the solution of the random initial value problems (RIVPs). Numerical simulation was carried out. Some properties of the random behaviour and the effect of the randomness were investigated.